Analysis of runoff variations in an arid catchment based on multi-model ensemble- a case study in the Tarim River Basin in Central Asia - Gao, Xiaoyu; Fang, Gonghuan; Chen, Yaning; Zhang, Xueqi (Frontiers in Earth Science, 2023)
This study delivers an interesting study about tracking the historical and future runoff changes of the four headstreams (the Kaidu, Aksu, Yarkand and Hotan rivers) in the Tarim River Basin. The authors found that Tarim's four headstreams showed an increasing trend during 1957-2022. The also used a SWAT-Glacier model to model runoff generations over the basin, and found that streamflow will continue to increase in the future, which is an important finding for the policy-makers of water resources management. I would recommend some minor revisions before acceptance.